Uma aplicacao da celula de comutacao ZVS-PWM-GEPAE ao conversor DC-AC - Mendes de Seixas, Falcondes Jose [UNESP]; Martins, Denizar Cruz [UNESP]; Barbi, Ivo [UNESP] (My University, 1996)
This work presents the design and procedure of a DC-to-AC converter using a ZVS Commutation Cell developed by Barbi and Martins (1991) and applied to the family of DC-to-DC PWM converters. Firstly, we show the cell applied to buck converter. The stages of operation and the main current and voltage equations of the resonant devices are presented. Next, we adapt the converter to the regenerative operation mode. Hence, the full bridge converter at low frequency operation is conected on the DC-to-DC stage (at high frequency) output ends (Seixas, 1993). Commutation of zero voltage for all switches, PWM at constant frequency and neither overvoltage nor additional current stress are observed by digital simulation. The design example and experimental results obtained by prototype rated at 275 V, 1 kW and 40 kHz are also presented.
Keywords: Computer simulation; Control system analysis; Electric commutation; Commutation cell; Direct current to alternating current converters; Power converters